Consumer Preferences for Sunco Cooking Oil as a Daily Necessity: Preferensi Konsumen terhadap Minyak Goreng Sunco sebagai Kebutuhan Harian - Akyun, Rizki Khurrota; Sari, Herlinda Maya Kumala (Indonesian Journal of Law and Economics Review, 2024)
Background: The fluctuating prices and availability of vegetable oils have raised concerns in consumer markets. Specific Background: Key factors like price, product quality, and promotion need closer examination to understand purchasing decisions. Knowledge Gap: Limited research addresses the combined impact of these factors on consumer behavior. Aims: This study aims to assess the influence of price, product quality, and promotion on oil purchasing decisions. Results: Based on quantitative analysis of 96 respondents, price, product quality, and promotion significantly affect purchasing decisions. Novelty: This research highlights the combined effect of these factors, offering new insights into consumer choices. Implications: The findings suggest that businesses should focus on competitive pricing, product quality, and effective promotions to boost sales. Highlights : Price, product quality, and promotion significantly influence oil purchasing decisions. A sample of 96 respondents was analyzed using multiple linear regression. Findings emphasize the importance of competitive pricing and strong promotional strategies. Keywords: Price, Product Quality, Promotion, Purchasing Decisions, Oil